Nexus between Student Engagement variables and their Academic Achievement in Quantitative Economics that aid entrepreneurship in Osun State, Nigeria - ADEBISI, Kehinde Lateef (Ilorin Journal of Education, 2025)
Quests for solutions to various economic crisis befalls Nigeria deserves multi-facet approaches, ranges from solution to educational problems to generation of engaged youth on entrepreneurship skill. Studies have shown that students are not properly skilled on quantitative analysis of economy. It was against this background that the study examined relationship between Students’ Engagement (intellectual engagement, emotional engagement and social engagement) and their achievement in Quantitative Economics. Expo facto design of correlational type was adopted for the study. The population comprised of all economics student in public secondary schools in Osun State. One thousand and eighty students were sampled from twenty-four schools in twelve local government areas across three senatorial districts in the state. Multi-stage sampling procedures were used. Two instruments were used; Students’ Engagement questionnaire (SEQ) and Quantitative Economics Achievement Test (QEAT). SEQ was validated using Cronbach Alpha with reliability coefficient of 0.91 while QEAT was validated using KR20 and the reliability coefficient was 0.88. Multiple regressions were used to analyse data collected. It was found that student achievement in Quantitative Economics is accounted for by certain percent of the predictor variables, and the ANOVA was significant. Three independent variables contributed significantly to prediction model at 0.05 Alpha level. The findings show that there is relationship between the independent variables and student achievement in Quantitative Economics. Therefore, students should be adequately engaged to improve their performance in quantitative aspects of economics as it is one of the aspects for developing entrepreneurship skill of the students.